A scientometric study on Spanish doctoral theses in tutorial action (1980-2016) - Salgado-Orellana, Norma; Ferrada, Cristian; Puraivan, Eduardo; Parraguez, Rafael (Revista General de Información y Documentación, 2018)
This study reveals the main characteristics of Spanish research related to tutorial action, through a scientometric analysis, of the doctoral theses indexed in the TESEO database for the period 1980-2016. The thesis search has been extended with related terms, delivered by the literature, recovering 245 doctoral theses. The tutorial action is a topic of great conceptual richness and may well be considered a topic of interest in research. The time series and the diachronic productivity have been elaborated in three cycles, in addition to other variables related to the content and methodologies. The findings show that their production has not yet achieved a logistical stability of growth, and the production of doctoral theses is concentrated in a small number of institutions and directors.